A data library of Candida albicans functional genomic screens. Issue 7 (23rd November 2021) - Gervais, Nicholas C; Halder, Viola; Shapiro, Rebecca S
ABSTRACT: Functional genomic screening of genetic mutant libraries enables the characterization of gene function in diverse organisms. For the fungal pathogen Candida albicans, several genetic mutant libraries have been generated and screened for diverse phenotypes, including tolerance to environmental stressors and antifungal drugs, and pathogenic traits such as cellular morphogenesis, biofilm formation and host–pathogen interactions. Here, we compile and organize C. albicans functional genomic screening data from ∼400 screens, to generate a data library of genetic mutant strains analyzed under diverse conditions. For quantitative screening data, we normalized these results to enable quantitative and comparative analysis of different genes across different phenotypes. Together, this provides a unique C. albicans genetic database, summarizing abundant phenotypic data from functional genomic screens in this critical fungal pathogen. Abstract : Mining the literature to generate a database of genetic screens in an important fungal pathogen enables increased data accessibility and promotes an understanding of gene function.